Cultivating Soft Skills and Technical Expertise: Identifying Effective Pedagogical Approaches for Civil Aviation Cabin Crew Training (Journal of Interdisciplinary Insights, 2024)
This study investigates the effectiveness of pedagogical approaches in cultivating both soft skills and technical expertise among civil aviation cabin crew trainees at Hebei Minzu Normal University. Through a mixed-method approach combining literature review and quantitative data collection via a survey questionnaire, the research assesses the perceptions and experiences of 150 current cabin crew students. The findings indicate that while the training program is effective in developing technical competencies, there is a need for better integration of soft skills training. High levels of satisfaction were reported for the curriculum's technical components, but there is room for improvement in combining these with interpersonal skills development. The study highlights the importance of hands-on experiential learning, industry exposure, and continuous feedback mechanisms to bridge the gap between academic training and industry demands. Recommendations are made to enhance curriculum relevance, improve teaching methodologies, support soft skills development, and ensure continuous program evaluation and improvement.